The pathogenesis of tuberculosis - Bishai, William R. (Henry Stewart Talks, 2013)
TB disease, The tubercle bacillus, The natural history of TB, M.tb. initial infection, Granuloma formation, Latent TB, Active TB, TB and HIV, Animal models of TB pathogenesis
Archived at 2021/11/28